Analysis of factors of influence on the development of tourism space of the European Union - Sklyarenko, Yaroslava; Khanova, Elena (Technology audit and production reserves, 2018)
The object of research is the tourist space of the European Union (EU). One of the most problematic places is the significant territorial diversity of the European tourist space, manifested by a different level of development of the tourism industry. The segmentation of the European space is done according to the level of development of the tourism industry with the help of the cluster model and the allocation of 7 clusters of EU countries by the level of development of the tourism industry. It is concluded that with regard to the hierarchy of sub-indices, the resource component and, accordingly, the natural and cultural resources sub-index has the greatest value in the segmentation process of the EU countries by the level of development of the tourism industry. The “Public policy and the creation of favorable conditions in the field of travel and tourism” and “Infrastructure” sub-indices have about the same significance for the segmentation of the EU countries by the level of development of the tourism industry. The smallest value in the segmentation process is occupied by the “Favorable environment” sub-index. In the course of the study, a factor analysis is conducted to determine significant factors in the development of the tourism industry for each segment (cluster) to further develop the main aspects of tourism policy. The conclusion is made about the significant weight of the favorable environment for such countries as Austria, Greece, Denmark, Portugal, Finland, Sweden, Estonia, Latvia, and Lithuania. The development of public policy and the creation of favorable conditions in the field of travel and tourism are especially important for countries such as Austria, Greece, Denmark, Portugal, Finland, Sweden, the United Kingdom, the Netherlands, and France. Infrastructure development is a significant factor in the development of all countries of the European tourist space, however, it has the greatest influence for such countries as: Great Britain, the Netherlands, France, Spain, Italy, Germany, Spain, Italy, Cyprus, Malta. The resource component of the development of the tourism industry most influences the development of the tourism industry in such countries as Spain, Italy, Germany, Luxembourg, Ireland. This provides the opportunity to segment the European tourist competitive space with the subsequent improvement of the tourist policy of the European Union.